Hydrophilic Carbon Nanomaterials: Characterisation by Physical, Chemical, and Biological Assays. (22nd February 2019) - Veloso, Andreia D.; Ferraria, Ana M.; Botelho do Rego, Ana M.; Tavares, Pedro B.; Valentão, Patrícia; Pereira, David D.; Andrade, Paula B.; Fernandes, António J.; Oliveira, Maria C.; Videira, Romeu A.
Abstract: A highly hydrophilic carbon nanomaterial was generated by using an electrochemical approach, and its structure, chemical composition, redox properties, antioxidant activity and effects on cells were characterised. It was found that the nanomaterial possesses a structure dominated by sp 2 carbon atoms in a non‐ordered carbon network formed by small clusters (<2 nm) of a carbonaceous material. This material has an outstanding capability for donating electrons and an unusual ability to bind metal cations. Antioxidant activity assays showed that it displays a high scavenging activity against both 2, 2‐diphenyl‐1‐picrylhydrazyl and 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) radicals, and a concentration‐dependent ability to protect mitochondrial lipids and intracellular thiol groups from oxidation promoted by external oxidising agents. Cell‐based assays also revealed that the nanomaterial has the ability to protect neuronal cells against oxidative damage and toxicity promoted by tert ‐butyl hydroperoxide and amyloid‐β1–42 peptide. These results, combined with the attractive methodology for generating this hydrophilic carbon‐based nanomaterial, make this study the first step in addressing the therapeutic application of this new material. Abstract : A redox balancing act : A hydrophilic carbon nanomaterial was synthesised from graphite using an electrochemical approach. This material has a strong electron‐donor capacity, consistent with its exceptional antioxidant activity. This nanomaterial affords cell protection against the toxicity induced by the amyloid‐β1–42 peptide and oxidants, from which we envisage major breakthroughs in therapeutic nanotechnology.